Implikasi Kebijakan Pengampunan Bersyarat terhadap Tingkat Residivisme pada Kasus Tindak Pidana Narkotika di Indonesia - Jamaludin, Robby; Priyambodo, Mas Agus (HUMANIORUM, 2025)
Drug offenses and the persistent issue of recidivism among narcotics offenders pose significant challenges to Indonesia's legal system. Conditional release, or Pembebasan Bersyarat, is a policy intended to reintegrate inmates back into society under specific conditions. This study examines the implications of conditional release policies on the recidivism rates of narcotics offenders in Indonesia, considering the stringent requirements set forth by national regulations. The research aims to provide a deeper understanding of the effectiveness of this policy in preventing repeat offenses. This study employs a qualitative approach, grounded in a normative legal framework, to analyze the existing legal principles and regulations related to conditional release and their implementation in the context of narcotics offenses. Data collection involves the use of primary and secondary sources, with a focus on literature review and qualitative analysis to draw conclusions from the findings. The analysis of regulations reveals stringent requirements for narcotics offenders seeking conditional release, reflecting the perceived high risk of recidivism. Studies suggest that the effectiveness of conditional release in reducing recidivism is influenced by individual factors, social environment, and the quality of rehabilitation programs and post-release support. While conditional release aims to incentivize rehabilitation and reduce prison overcrowding, its actual impact on narcotics recidivism in Indonesia requires ongoing evaluation and improvement.